Case Report: Robotically Assisted Excision of Cystic Tumor Located in a Difficult to Access Area in the Liver - Solomonov, Evgeny; Tzadok, Itamar; Biswas, Seema (Frontiers in Surgery, 2021)
Introduction: Cystic liver lesions may be benign cysts, parasitic infestations or malignant tumors requiring surgical resection. Hilar location and relation to major vasculature present challenges in conventional surgical access and resection. Materials and Methods: We describe totally robotic excision of a cystadenoma in a 55-year-old woman without complication. Time points in the accompanying video (https://youtu.be/Tn_QPgpSHA4) are embedded within the text. Results: Advantages of the robotic technique lie in overcoming the natural restriction of conventional laparoscopic instruments, easier repair and control of intraoperative vascular injuries using EndoWrist® instruments, ergonomic dissection close to major vasculature and reduced intraoperative blood loss as dissection is easier. Discussion: Indications for robotic surgery included the large size of the cystic lesion, its intrahepatic location, and compression of the inferior vena cava (IVC) and right and middle hepatic veins. Had robotic removal of the lesion not been feasible, the entire lobe of the liver would have required resection.